2013
DOI: 10.1186/1472-6920-13-84
|View full text |Cite
|
Sign up to set email alerts
|

Teaching ultrasound in a curricular course according to certified EFSUMB standards during undergraduate medical education: a prospective study

Abstract: BackgroundAs a non-invasive and readily available diagnostic tool, ultrasound is one of the most important imaging techniques in medicine. Ultrasound is usually trained during residency preferable according to German Society of Ultrasound in Medicine (DEGUM) standards. Our curriculum calls for undergraduate training in ultrasound of medical students in their 4th year of undergraduate education. An explorative pilot study evaluated the acceptance of this teaching method, and compared it to other practical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 32 publications
5
78
0
2
Order By: Relevance
“…One way of assessing students is to use the national sonographer standard [5]; however, this standard will vary between countries. Although medical students can reach national sonographer standards with a structured integrated approach [5], the majority of student scores tended to be akin to 'a borderline level of competency'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One way of assessing students is to use the national sonographer standard [5]; however, this standard will vary between countries. Although medical students can reach national sonographer standards with a structured integrated approach [5], the majority of student scores tended to be akin to 'a borderline level of competency'.…”
Section: Discussionmentioning
confidence: 99%
“…Some [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Fifteen papers describe variously integrated ultrasound curricula. Five studies are notable for the numbers of medical students involved in a formal evaluative process (>150) [5][6][7][8][9]. Heinzow et al [5] reported that students were evaluated as per DEGUM standards (national sonographer examination standards).…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 1 more Smart Citation
“…While it could be argued that students would recognize the questions in their post-course evaluation, we did not inform them about the right answers or their scores before or after the course to ensure that they -and students taking the seminar in the futureremained blind to the results. A similar approach has been used by other authors [11,12]. Most of the students also considered dermatologic ultrasound to be helpful in studying dermatology as a subject (LS 1.90; 80 % agree or strongly agree).…”
mentioning
confidence: 82%
“…Students' perception of their confidence in performing ultrasound examinations was also lower than the rest of items with a (LS 2; 68.57 % agree or strongly agree). This problem could be solved by increasing the number of ultrasound scans using simulators, by increasing the amount of tutors by recruiting students from previous groups [13,14], and by introducing hand-held devices [15,16].…”
mentioning
confidence: 99%